CZM-based FE numerical study on pull-out performance of adhesive bonded-in-rod (BiR) joints for timber structures. (December 2022) - Bedon, C.; Rajcic, V.; Barbalic, J.; Perkovic, N.
Abstract: Bonded-in-Rod (BiR) connections for timber structures are becoming rather popular solution, in place of other traditional fastening techniques. Besides, design rules and recommendations in support of safe and robust verification are still poor in existing standards. As such, the actual mechanical performance and load-bearing capacity – which is severely affected by a multitude of operational parameters – should be possibly addressed with the support of experimental investigations. In this paper, a Cohesive Zone Modelling (CZM) based, Finite Element (FE) numerical investigation is proposed for a total of 144 BiR joints characterized by various geometrical and mechanical properties, including grain orientation (α = 0° or 90°), adhesive type (polyurethane or epoxy glue), diameter ( d = 10, 14, 20 mm) and anchorage length of rods ( L = 60, 100, 200, 400 mm) is presented. Most importantly, the attention is also focused on the analysis of service class effects / moisture content (9, 18 or 27 %) on the actual residual capacity of the examined joints, which is of paramount importance for safe design applications in timber structures. Based on validation of input model properties to past experimental results, the sensitivity of basic mechanical performance indicators for the examined BiR samples is discussed in the paper.